A Phase I Pharmacokinetic and Bioavailability Study of a Sublingual Fentanyl Wafer in Healthy Volunteers - Lim, Stephen; Schug, Stephan; Sunderland, Bruce; Paech, Michael; Liu, Yandi (Lippincott Williams & Wilkins, 2012)
Background: The sublingual administration of opioids is a simple and noninvasive method that provides rapid analgesia. In this phase I study we investigated the pharmacokinetics and bioavailability of a fentanyl wafer in healthy volunteers. The principal study objective was to investigate the pharmacokinetic profile of a new sublingual fentanyl wafer and to establish its absolute bioavailability. Methods: Twenty-four healthy volunteers, mean age 23 years, were randomly assigned to receive the equivalent of fentanyl 100 μg by both the sublingual and IV routes. Blood samples were collected in sterile polypropylene tubes for 24 hours after each fentanyl administration. The pharmacokinetic parameters were determined by model-independent pharmacokinetic analyses of the plasma fentanyl concentration–time profiles. Results: The mean absolute bioavailability of the sublingual fentanyl wafer was 78.9% (90% confidence interval [CI] 51.1% to 121.7%). The first detectable plasma fentanyl concentration time ranged from 2 to 10 minutes in all volunteers, and the mean (±SD) time to peak plasma concentration at 0.91 (±0.73) hours after administration. Conclusion: Sublingual administration of fentanyl as a wafer product resulted in rapidly detectable plasma fentanyl concentrations. The absolute bioavailability of 78.9% indicated a high systemic availability of fentanyl and suggests that further development of this wafer is justified.